The scientometric evaluation of the research on the algae and bio-energy - Konur, Özcan (ELSEVIER SCI LTD, 2011)
The present study explores the characteristics of the literature on the algae and bio-energy published during the last three decades, based on the database of Science Citation Index-Expanded (SCIE) and Social Sciences Citation Index (SSCI) and its implications using the scientometric techniques. The results of this work reveal that the literature on the algae and bio-energy has grown exponentially during this period reaching 717 papers in total. Most of document type is in the form of journal articles, reviews, and proceedings, constituting 98% of the total literature and English is the predominant language (97.6%). USA, China, Germany, and England are the four biggest contributing countries on the algae and bio-energy literature publishing, 26%, 8%, 8%, and 8% of the sample, respectively. The Chinese Academy of Sciences is the largest institutional contributor publishing 2.6% of the papers. The most publishing four authors are Wilhelm (13 papers) followed by Wu (15 papers), Mimuro (10 papers), and Zhao (9 papers). "Bioresource Technology" is the most publishing journal with 24 published papers, followed by "Journal of Applied Phycology" (17 papers). and "Biotechnology and Bioengineering" (15 papers). "Biotechnology & Applied Microbiology" is the subject area with 24.3% of the sample published. This is followed by "Energy & Fuels" (16.3%), "Marine & Freshwater Biology" (14.2%), and "Environmental Sciences" (12.3%). The total number of citations is 11,079, giving a ratio for the "Average Citations per Item" as 15.45 and "H-index" as 52. A list of most-cited 25 authors is produced and Chisti (2007) receives 320 citations with 80 total average citations per year. This paper is followed by Lewis and Nocera (2006; 296 citations). Demirbas (2001; 187 citations). Chisti (2007) has the highest impact on the literature on the algae and energy with total average citations per year of 80. This is followed by Lewis and Nocera (2006, 59.8 annual citations) and Chisti (20(18, 41 annual citations). An analysis of the citing papers shows the impact of the research on the algae and bio-energy for the related academic disciplines. This provides further incentives for all the stakeholders of the research on the algae and energy, but especially for the researchers and their institutions and their countries to do more research in this area. The results of this first ever such study of its kind show that the scientometric analysis has a great potential to gain valuable insights into the evolution of the research the on algae and bio-energy as in the case of new emerging technologies and processes such as nanoscience and nanotechnology complementing literature reviews, content analysis and metaanalysis research techniques. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Algae; Microalgae; Bio-energy; Scientometrics; Biofuels; Research evaluation